Pemberdayaan Teknologi SI-NILA Berbasis Internet Of Things Pada Kelompok Budidaya Ikan Nila di Desa Penarukan - Anak Agung Gde Ekayana; Peter Enlarga Lauda (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Penarukan Village, located in Tabanan Regency, is predominantly inhabited by communities engaged in freshwater fish farming, particularly Nile tilapia (Oreochromis niloticus). The high demand for Nile tilapia in Tabanan and surrounding areas poses a challenge for farmers to manage the growth and development of the fish to ensure optimal quality. During the cultivation process, various issues arise that require effective solutions to support the sustainability of this sector. One of the main problems faced by fish farmers is related to the quality of biofloc pond water, which is still monitored using conventional methods. Poor water quality that does not meet the optimal living standards for Nile tilapia can hinder growth, reduce fish health, and negatively impact production yield. Manual monitoring methods are also prone to inaccuracy and complicate the data analysis process needed for effective decision-making.To address this issue, a technology-based solution has been proposed in the form of a real-time monitoring system using the “SI-NILA” mobile application integrated with a microcontroller-based Internet of Things (IoT) system. This system allows for continuous monitoring of pond water quality and automated pH control to maintain suitable conditions for fish growth. This innovation is expected to improve efficiency and effectiveness in fish farming practices, minimize the risk of crop failure, and promote the digital transformation of aquaculture in Penarukan Village, contributing to the sustainable development of the freshwater aquaculture sector.